Pengaruh Media Flash Card terhadap Kemampuan Mengenal Huruf Siswa Kelas 2 SD Negeri 20 Mabah - Ronia Belin; Fransisco Adam (Pusat Riset dan Inovasi Nasional, 2026)
The ability of flashcard learning media has been proven to have a positive impact on 17 second-grade students of SD Negeri 20 Mabah in recognizing letters. Applying a single-group experimental design, this study compared learning achievements through pre-test and post-test. And then produced an increase from the initial score of 46.17 to 85.88. Statistical evidence through a t-test (p <0.05) ensures that this teaching aid is an effective solution to optimize the ability to recognize letters at the elementary school level. These results indicate that the use of simple visual media can increase student interest and engagement in the learning process. Flashcards help students understand the shape and sound of letters more concretely through interactive learning activities. Thus, this media can be recommended as an alternative strategy for early reading learning in elementary schools. In addition, the use of flashcards can also create a more enjoyable learning atmosphere so that students are more motivated to practice recognizing letters.